Evaluación de la bioseguridad en granjas porcinas de la provincia de Zamora Chinchipe - Castillo Gálvez., Juan Pablo (2025)
Biosecurity strategies, together with proper production management, encompass all actions aimed at preventing the introduction of pathogens into swine farms and their subsequent dissemination within the facilities. This study evaluated biosecurity practices in industrial and traditional swine farms in Zamora Chinchipe, Ecuador, using a survey directed to the owners. The evaluation was conducted using the Biocheck online questionnaire (https://biocheckgent.com/es) on 35 pig farms, of which 26 were traditional and 9 were industrial. The overall mean biosecurity score was 47.30 ± 9.23 %. Both external biosecurity (46.66 ± 7.27 %) and internal biosecurity (47.94 ± 12.98 %) obtained low scores, showing that biosecurity in this region is poor. Within external biosecurity, the weakest score was observed in the subcategory of visitors and farm workers (14.14 ± 12.97 %), in addition, there was a difference between the type of farms in the subcategory of rodent and bird control (p = 0.01). Concerning internal biosecurity, the lowest score was observed in the subcategory of cleaning and disinfection (33.23 ± 20.80 %); a statistical difference was also observed between farm type in the subcategory of disease management (p = 0.001) and cleaning and disinfection (p = 0.01). This study reveals that biosecurity measures on pig farms in Zamora Chinchipe are below the Ecuadorian and world average. Therefore, it is necessary to focus on improving the uniformity of biosecurity practices to align more closely with international standards and improve protection against disease transmission. Key words: Production, Pigs, Biosecurity.